JOINT AND SEGMENTATION DESIGN ON PAPER PUPPETS FOR CAT CHARACTERS IN CUT OUT STOP MOTION ANIMATION - Dominika Anggraeni Purwaningsih (Universitas Multimedia Nusantara, 2019)
Stop motion, particularly paper cut out animation, is one of the oldest yet surviving animation techniques to date. Similar to other traditional animation techniques, it offers appealing looks unique to its nature. With the development of new technologies, stop motion continues to evolve. Paper puppet act as actor, therefore it’s the most essential element in production of paper cut out animation. Careful designs have to be made to ensure movements can be performed well by animators. The biggest question when designing puppets are how do we divide the parts (segmentation) and what kind of mechanism should we use to connect these parts (joint)? Several factors are to be considered when deciding the right approach for the answer. This qualitative research will use both observation and experiment method. Observation is conducted by studying existing paper puppets from other paper cut out animation shorts, tutorials, commercials, and behind the scenes videos from the filmmaker. Following the observation is an experiment where the author will use the data to explore paper puppets making, comparing benefits and weaknesses, and adjust the final method to comply the needs of the short animation project titled “Spay & Neuter” where the final design of the cat puppets will be applied.